A low dose adenovirus vectored vaccine expressing Schistosoma mansoni Cathepsin B protects from intestinal schistosomiasis in mice - Dilhan J. Perera; Adam S. Hassan; Sunny S. Liu; Seyyed Mehdy Elahi; Christine Gadoury; Risini D. Weeratna; Rénald Gilbert; Momar Ndao (EBioMedicine, 2022)
Summary: Background: Schistosomiasis is an underestimated neglected tropical disease which affects over 236.6 million people worldwide. According to the CDC, the impact of this disease is second to only malaria as the most devastating parasitic infection. Affected individuals manifest chronic pathology due to egg granuloma formation, destroying the liver over time. The only FDA approved drug, praziquantel, does not protect individuals from reinfection, highlighting the need for a prophylactic vaccine. Schistosoma mansoni Cathepsin B (SmCB) is a parasitic gut peptidase necessary for helminth growth and maturation and confers protection as a vaccine target for intestinal schistosomiasis. Methods: An SmCB expressing human adenovirus serotype 5 (AdSmCB) was constructed and delivered intramuscularly to female C57BL/6 mice in a heterologous prime and boost vaccine with recombinant protein. Vaccine induced immunity was described and subsequent protection from parasite infection was assessed by analysing parasite burden and liver pathology. Findings: Substantially higher humoral and cell-mediated immune responses, consisting of IgG2c, Th1 effectors, and polyfunctional CD4+ T cells, were induced by the heterologous administration of AdSmCB when compared to the other regimens. Though immune responses favoured Th1 immunity, Th2 responses provided by SmCB protein boosts were maintained. This mixed Th1/Th2 immune response resulted in significant protection from S. mansoni infection comparable to other vaccine formulations which are in clinical trials. Schistosomiasis associated liver pathology was also prevented in a murine model. Interpretation: Our study provides missing preclinical data supporting the use of adenoviral vectoring in vaccines for S. mansoni infection. Our vaccination method significantly reduces parasite burden and its associated liver pathology - both of which are critical considerations for this helminth vaccine. Funding: This work was supported by the Canadian Institutes of Health Research, R. Howard Webster Foundation, and the Foundation of the McGill University Health Centre.